Continuous treatment with odanacatib for up to 8 years in postmenopausal women with low bone mineral density: a phase 2 study. Issue 6 (June 2016) - Rizzoli, R.; Benhamou, C.-L.; Halse, J.; Miller, P.; Reid, I.; Rodríguez Portales, J.; DaSilva, C.; Kroon, R.; Verbruggen, N.; Leung, A.; Gurner, D.
Abstract Summary The efficacy and safety of weekly oral odanacatib (ODN) 50 mg for up to 8 years were assessed in postmenopausal women with low bone mineral density (BMD). Treatment with ODN for up to 8 years resulted in continued or maintained increases in BMD at multiple sites and was well tolerated. Introduction ODN is a selective inhibitor of cathepsin K. In a 2-year phase 2b study (3/10/25/50 mg ODN once weekly [QW] or placebo) and extensions (50 mg ODN QW or placebo), ODN treatment for 5 years progressively increased BMD and decreased bone resorption markers in postmenopausal women with low BMD (ClinicalTrials.gov NCT00112437). Methods In this prespecified interim analysis at year 8 of an additional 5-year extension (years 6 to 10), patients (n  = 117) received open-label ODN 50 mg QW plus weekly vitamin D3 (5600 IU) and calcium supplementation as needed. Primary end points were lumbar spine BMD and safety. Patients were grouped by ODN exposure duration. Results Mean (95 % confidence interval [CI]) lumbar spine BMD changes from baseline were 4.6 % (2.4, 6.7; 3-year continuous ODN exposure), 12.9 % (8.1, 17.7; 5 years), 12.8 % (10.0, 15.7; 6 years), and 14.8 % (11.0, 18.6; 8 years). Similar patterns of results were observed for BMD of trochanter, femoral neck, and total hip versus baseline. Geometric mean changes from baseline to year 8 for bone resorption markers were approximately −50 % (uNTx/Cr) and −45 % (sCTx), respectively (all groups); bone formation markers remained near baseline levels. No osteonecrosis of the jaw, delayed fracture union, or morphea-like skin reactions were reported. Conclusions Treatment with ODN for up to 8 years resulted in gains in BMD at multiple sites. Bone resorption markers remained reduced, with no significant change observed in bone formation markers. Treatment with ODN for up to 8 years was well tolerated.